Rare case of alimentary butylbiphenyl intoxication - Šimčík, Damián; Voříšek, Viktor; Jakl, Martin (Journal of Applied Biomedicine, 2022)
BACKGROUND: Unexpected accidental intoxication by uncommon industrial substances is a rare, but challenging and perilous event. To our best knowledge, this is the first reported case of 3,4',5,6'-tetra-tert-butylbiphenyl-2,3'-diol intoxication. CASE REPORT: A 20-year-old man was referred to the Department of Emergency Medicine after seven days of nausea and vomiting triggered by drinking mead. Very high doses of 3,4',5,6'-tetra-tert-butylbiphenyl-2,3'-diol were detected in mead, blood, and urine samples. To prove the intoxication, gas chromatography - ion trap was performed. Symptoms of intoxication persisted for two weeks without significant organ damage. The case report illustrates the need for a multistep approach, focused mainly on the analysis of possible sources of intoxication.
Keywords: chromatografie plynová; Vomiting; Chromatography, Gas; dospělí; Young Adult; Humans; nauzea; Adult; mladý dospělý; zvracení; mužské pohlaví; Nausea; lidé; Male